Macrophage produced IL-12p70 mediates hemorrhage-induced damage in a complement dependent manner - Hylton, Diana J.; Hoffman, Sara M.; Van Rooijen, N.; Tomlinson, Stephen; Fleming, Sherry D. (My University, 2013)
Hemorrhage and hemorrhagic shock instigate intestinal damage and inflammation. Multiple components of the innate immune response, including complement and neutrophil infiltration, are implicated in this pathology. To investigate the interaction of complement activation and other components of the innate immune response during hemorrhage, we treated mice post-hemorrhage with CR2-fH, a targeted inhibitor of the alternative complement pathway and assessed intestinal damage and inflammation 2 h after hemorrhage. In wildtype mice, CR2-fH attenuated hemorrhage-induced, mid-jejunal damage and inflammation as determined by decreased mucosal damage, macrophage infiltration, LTB[subscript 4], IL-12p40, and TNF-α production. The critical nature of intestinal macrophage infiltration and activation in the response to hemorrhage was further determined using mice pre-treated with clodronate containing liposomes. The absence of either macrophages or IL-12p70 attenuated intestinal damage. These data suggest that complement activation and macrophage infiltration with IL-12p70 production are critical to hemorrhage induced mid-jejunal damage and inflammation.
Keywords: Inflammation; Mouse; Intestine; Cytokines; Complement inhibitor